2013
DOI: 10.1128/mcb.00225-13
|View full text |Cite
|
Sign up to set email alerts
|

The Keap1-Nrf2 System Prevents Onset of Diabetes Mellitus

Abstract: e Transcription factor Nrf2 (NF-E2-related factor 2) regulates a broad cytoprotective response to environmental stresses. Keap1 (Kelch-like ECH-associated protein 1) is an adaptor protein for cullin3-based ubiquitin E3 ligase and negatively regulates Nrf2. Whereas the Keap1-Nrf2 system plays important roles in oxidative stress response and metabolism, the roles Nrf2 plays in the prevention of diabetes mellitus remain elusive. Here we show that genetic activation of Nrf2 signaling by Keap1 gene hypomorphic knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
263
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 291 publications
(283 citation statements)
references
References 44 publications
17
263
1
2
Order By: Relevance
“…Further supporting this complex role of Nrf2, recent studies have shown that overexpression of Nrf2 through the use of graded knockdown of Keap1 actually provides protection against the onset of diabetes in genetic models of diabetes in mice (79). This suggests a beneficial role for Nrf2 in the protection against the development of diabetes with increased expression of Nrf2 resulting in decreased blood glucose and protection against obesity in a db/db mouse background.…”
Section: ) Was Not Altered In Nrf2mentioning
confidence: 86%
“…Further supporting this complex role of Nrf2, recent studies have shown that overexpression of Nrf2 through the use of graded knockdown of Keap1 actually provides protection against the onset of diabetes in genetic models of diabetes in mice (79). This suggests a beneficial role for Nrf2 in the protection against the development of diabetes with increased expression of Nrf2 resulting in decreased blood glucose and protection against obesity in a db/db mouse background.…”
Section: ) Was Not Altered In Nrf2mentioning
confidence: 86%
“…This is illustrated by the oxidative stress-response regulated by NRF2, which prevents the onset of diabetes 80 , systemic lupus erythematosus 81 , rheumatoid arthritis 82 and multiple sclerosis 83 in murine models for these diseases. Damage responses also exert protective effects against autoimmune diseases, as illustrated for the UPR in the context of type 1 diabetes, where impaired expression of the the UPR components activating transcription factor 6 (ATF6) and XBP1 in -cells of the pancreas are associated with disease progression in both mice and humans 84 .…”
Section: Tissue Damage Control In Non-communicable Diseasesmentioning
confidence: 99%
“…Loss of Keap1 in hematopoietic cells suppresses differentiation toward the erythroid lineage (82), so the anemia in NEKO mice is likely due to a lack of Keap1 in hematopoietic cells. Growth retardation in NEKO mice might be caused by Nrf2 activation in skeletal muscle and adipose tissue, because Keap1 deletion in skeletal muscle reduces body weight (83), and loss of Keap1 represses the differentiation of adipose cells (84).…”
Section: Novel Function Of Nrf2mentioning
confidence: 99%